ANÁLISE DO EFEITO DO MELOXICAM NANOENCAPSULADO EM DIFERENTES MODELOS DE DOENÇAS ASSOCIADAS A INFLAMAÇÃO EM CAMUNDONGOS - Ianiski, Francine Rodrigues (2016)
Nanoparticles are considered systems of great interest for medicine, since they can enhance the therapeutic effects of various active as anti-inflammatories, such as meloxicam. The inflammatory process is associated with several diseases. Thus, in the present study, we investigated the pharmacological action of nanoencapsulated meloxicam, pegylated or not, using diseases animal models, associated with inflammation in mice. First, to evaluate the time/response curve of meloxicam loaded-nanocapsules (NC-M) and free meloxicam (M-F) was carried out acute inflammation model (pleurisy) induced by carrageenan (Cg) in male adult Swiss mice (20-25g). Subsequently, it was performed the evaluation of NC-M and M-F effects in Alzheimer's disease (AD) model induced by β-amyloid peptide (βa) in male adult Swiss mice (20-25g). Later, in order to reduce some of challenges that hinder the use of nanoparticles in clinical practice, we tried to coat the nanocapsules with polyethylene glycol (PEG), protecting the nanoparticles from recognition by opsonin and prolonging the circulation time. Finally, we evaluated the effect of nanocapsules containing meloxicam and coated with PEG (NCPEG-M) and M-F in a Parkinson's disease (PD) model induced by the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) in male adult C57/black mice (20-25g). For experimental models (pleurisy, AD and PD), mice were divided into six groups: control; induced; nano; free; induced-nano; and free-induced. The animals of control and induced groups received suspensions without meloxicam, mice belonging to nano and induced-nano groups received nanoencapsulated meloxicam (NC-M or NCPEG-M), while the animals of free and free-induced groups received free drug (M-F). Nanoencapsulated and free meloxicam were administered at dose of 5 mg/kg by gavage. In pleurisy model, it was observed that the treatment with the NC-M had a beneficial effect higher than M-F against the increase in total and differential of leukocytes, and in cytokines and of acid α-1-glycoprotein levels induced Cg in the pleural exudate. In AD, the NC-M reversed the memory and learning deficit and the changes on the Na+/K+-ATPase and cyclooxygenase (COX)-2 activities induced by βa in the hippocampus of mice, whereas the M-F only reversed the COX-2 activity. Also in this model, it was found that AD induced by βa peptide, in the short-term, is not a determining factor for reproducing the enzymatic modifications of creatine kinase, adenylate kinase and pyruvate kinase activities observed in the brains of post-mortem patients with AD. Based on the results obtained in models of pleurisy and AD, it can be seen that the NC-M showed anti-inflammatory effect. However, in order to improve the pharmacological effect of NC-M, particularly in diseases that affect the central nervous system, NC-M were coated with PEG and characterized. The NCPEG-M had an average particle diameter of 261 ± 13 nm, polydispersity index of 0.15 ± 0.07, pH values of 5.0 ± 0.2 and zeta potential values of -37.9 ± 3.2 mV. Furthermore, suspensions containing NCPEG-M provided to be highly homogeneous with a narrow size distribution with pH and zeta potential suitable. Pharmacological effect of NCPEG-M was tested in PD model. It was noted that the NCPEGM improved motor and nesting changes, and biochemical changes induced by MPTP, while the M-F had no effect. In this context, we can conclude that NC-M, pegylated or not, exhibited a superior pharmacological effect than free active in different models of diseases related to inflammation in mice.